Relationship between Leg Length and Foot Frequency with 50-Meter Running Speed - Ishak, Muhammad; Amahoru, Nurul Musfira (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to determine the relationship between leg length and foot frequency with a running speed of 50 meters. This research is a type of descriptive research. The population of this study is all students of SMP Negeri 8 Makassar with a research sample of 60 male students selected by random sampling. The data analysis technique used is a correlation and regression analysis technique using the SPSS Version 20.00 systematasignificantlevelof95%or 0.05.Basedontheresultsofdataanalysis,thisstudyconcludes that: There is a significant relationship between leg length and running speed of 50 meters, it is proven that the value of ro = 0.866 (P <  0.05); There was a significant relationship between the frequency of footsteps and the running speed of 50 meters, it was proven that the value of ro = 0.870 (P <  0.05); There was a relationship between leg length and footstep frequency with a running speed of 50 meters, proving a Ro value = 0.883 (P <  0.05).